2015
DOI: 10.1016/j.juro.2014.12.093
|View full text |Cite
|
Sign up to set email alerts
|

The Renal Effects of Prenatal Testosterone in Rats

Abstract: Prenatal testosterone induces proteinuria in adulthood. This effect is mediated via androgen receptor. Additional effects seem to be sex specific. Further studies should focus on the timing and dosing of testosterone as well as the applicability to human development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…Thus, sexual dimorphism in renal organogenesis as early as the third trimester in the human species could be related to testosterone secretion by male fetuses in utero [ 98 ]. Studies of prenatal exposure to testosterone have shown that the developing kidney is sensitive to testosterone [ 99 ], but its implication on renal development under physiological conditions in the fetus, as well as the molecular interaction between androgen signaling pathway and other signaling pathways implicated in nephrogenesis, remain to be further demonstrated.…”
Section: Gender Differences In Kidney Development and Organogenesismentioning
confidence: 99%
“…Thus, sexual dimorphism in renal organogenesis as early as the third trimester in the human species could be related to testosterone secretion by male fetuses in utero [ 98 ]. Studies of prenatal exposure to testosterone have shown that the developing kidney is sensitive to testosterone [ 99 ], but its implication on renal development under physiological conditions in the fetus, as well as the molecular interaction between androgen signaling pathway and other signaling pathways implicated in nephrogenesis, remain to be further demonstrated.…”
Section: Gender Differences In Kidney Development and Organogenesismentioning
confidence: 99%